2012
DOI: 10.1111/j.1523-5378.2011.00917.x
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural and Dietary Practices Among Malay Subjects in the North‐Eastern Region of Peninsular Malaysia: A Region of Low Prevalence of Helicobacter pylori Infection

Abstract: Under the assumption that sanitary, sociocultural, and dietary habits have not changed over the years, we can conclude that an increased risk of H. pylori was associated with unsanitary practices whereas protection was associated with consumption of tea and locally produced foods, "pegaga" and "budu." These dietary factors are candidates for future study on the effects on H. pylori transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
3
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 34 publications
3
41
3
5
Order By: Relevance
“…Interestingly, Abebaw et al (17) found hand washing before meals was associated with higher prevalence of H. pylori , and hand washing after using toilet carried no association with H. pylori prevalence. However, this result conflicts with what is generally understood about this association, and other studies reviewed here found that hand washing “not always” after toilet and “not always” before meal were associated with higher H. pylori prevalence (19). …”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Abebaw et al (17) found hand washing before meals was associated with higher prevalence of H. pylori , and hand washing after using toilet carried no association with H. pylori prevalence. However, this result conflicts with what is generally understood about this association, and other studies reviewed here found that hand washing “not always” after toilet and “not always” before meal were associated with higher H. pylori prevalence (19). …”
Section: Resultscontrasting
confidence: 99%
“…Of the nine studies included in this review, two were conducted in eastern China (11, 12), two in South Korea (13, 14), two in North America (15, 16), and one each in Ethiopia (17), India (18), and Malaysia (19). All studies focused on populations at increased risk for gastric cancer, except the US population-based survey to assess and promote awareness (15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that local practices or environmental factors may limit transmission or inhibit the infection. In a case-control study involving 161 Malay subjects (79 tested positive for H. pylori or "cases" and 82 tested negative for H. pylori or 'controls') from the state of Kelantan, some dietary factors were found to reduce risk of infection including frequent use of 'budu,' 'pegaga or Centenella asiatica ' and tea 20. Unidentified genetic or host factors intrinsic to this population may also result in them being less or have increased susceptibility to H. pylori infection or cancer as a whole.…”
Section: Organic Causes Of Dyspepsia Are Uncommon Among Malaysmentioning
confidence: 99%
“…Most recently, a review demonstrated that a plenty of dietary components, including specific foods, food components, and food products, were associated with H. pylori infection14. A case-control study from Malaysia found that frequent consumption of tea (OR: 0.023, 95% CI: 0.01–0.07), frequent use of ‘budu’ or local anchovy sauce (OR: 0.09, 95% CI: 0.1–0.7), and frequent use of local foods ‘pegaga’ or centenella asiatica (OR: 0.25, 95% CI: 0.1–0.65) were inversely associated with H. pylori infection15. However, regular diets consist of complex combinations of foods and nutrients ingested together may act independently or may interact with one another.…”
mentioning
confidence: 99%